Asymptomatic Bacterial Vaginosis Is Associated With Depletion of Mature Superficial Cells Shed From the Vaginal Epithelium - O'Hanlon, D. Elizabeth; Gajer, Pawel; Brotman, Rebecca M.; Ravel, Jacques (Frontiers in Cellular and Infection Microbiology, 2020)
Previous studies have described bacterial vaginosis (BV) as associated with increased cell-shedding from the cervicovaginal epithelium. Cell-shedding in excess of cell-proliferation is thought to decrease epithelial barrier function and increase susceptibility to infection. This study evaluated the number of shed cells in mid-vaginal smears from women with a diagnosis of symptomatic BV (sBV, n = 17), asymptomatic BV (aBV, n = 71), or no BV (n = 104) by Amsel criteria. The sBV smears contained significantly more shed cells (median 158/100X field) than no BV smears (median 91/100X field), p = 7.2e−9. However, we observed that aBV smears contained significantly fewer shed cells (median 35/100X field) than no BV smears, p = 22.0e−16. The sizes of cell-aggregates (cells shed in sometimes multilayered sections with intact cell-cell attachments) followed the same pattern. Cell-aggregates in sBV smears were significantly larger (median ~220,000 μm2) than those in no BV smears (median ~50,000 μm2), p = 1.8e−6, but cell-aggregates in aBV smears were significantly smaller (median ~7,000 μm2) than those in no BV smears, p = 0.0028. We also compared the superficial cell index (SCI), a measure of cervicovaginal epithelial cell maturity, in no BV and aBV smears with relatively low numbers of shed cells (≤50/100X field). The SCI of no BV smears was significantly higher (median 0.86) than that of aBV smears (median 0.35), p = 4.3e−98, suggesting a depletion of mature cells with exposure and shedding of underlying immature cells in aBV with low number of shed cells. These results indicate that aBV may contribute disproportionately to the increased susceptibility to reproductive tract infections associated with BV. Our findings remained true when considering only those smears in which the microbiota comprised a diverse set of strict and facultative anaerobic bacteria [Community State Type IV (n = 162)], thus excluding those dominated by Lactobacillus spp. This is consistent with our developing hypothesis that high-shedding sBV and low-shedding aBV could be temporally separated phases of the same condition, rather than two separate forms of BV. These findings might inform future work on clinical management of symptomatic and asymptomatic bacterial vaginosis.